SEJARAH DAKWAH DI LEMBAH PALU - Syamsuri Syamsuri (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2015)
There are three phases of the spread and development of Islam in Palu: mythological, ideological and scientific phases. In this paper, the figures of these three phases will be discussed. At this phase, the approach of Muslim scholars (ulama is to show natural symbols in spreading and teaching Islam. Spiritual power becomes a key of the success of ulama. There are three ulama who play a role in a mythological phase, Abdullah Raqi